615. Pharmacodynamics (PD) of the Beta-Lactamase Inhibitor Xeruborbactam When Administered in Combination with Meropenem. (15th December 2022) - Tarazi, Ziad; Roos, Niki; Page, Ted; Griffith, David
Abstract: Background: Xeruborbactam (XERU) is a member of a new class of cyclic boronic acid β-lactamase inhibitors with inhibitory activity against major members of Class A, B, C, and D beta-lactamases. The purpose of these studies was to determine the pharmacodynamic parameter that best described the activity of XERU against Enterobacterales and A. baumannii when administered in combination with a fixed dosage regimen of meropenem in the neutropenic mouse thigh infection model. 24h Free Xeruborbactam AUC vs CRE 24h Free Xeruborbactam AUC vs CRAB Methods: Seven carbapenem resistant Enterobacterales (CRE) and six carbapenem-resistant A. baumannii (CRAB) isolates were used in these studies. Mice were rendered neutropenic, infected with ∼10 7 CFU/thigh and were treated with various doses of XERU in combination with meropenem (300 mg/kg q2h) by the IP route starting 2 hours post infection for 24 hours. The meropenem dosage regimen was fixed and designed to simulate 2 g every 8 hours by 3-hour infusion in humans. Plasma exposures (PK) were measured in neutropenic, infected mice. The relationship between XERU PK-PD indices and the reduction in the log number of CFU per thigh were analyzed by using the sigmoid Emax PD model. Results: The activity of XERU was best described by the % 24h free XERU plasma concentrations exceeded 1 mg/L and 24h free xeru plasma AUC. Xeru PK-PD Parameters in Combination with Meropenem against CRE Xeru PK-PD Parameters in Combination with Meropenem against CRAB Conclusion: The PK-PD of XERU was best described by the % 24h free XERU plasma concentrations exceeded 1 mg/L and 24h free XERU plasma AUC. The PK-PD of XERU in combination with meropenem and the clinical PK of both drugs support further clinical development for the treatment of carbapenem-resistant isolates of Enterobacterales and A. baumannii. Disclosures: Ziad Tarazi, Qpex Biopharma: Employee Niki Roos, n/a, Qpex Biopharma: Employee Ted Page, n/a, Qpex Biopharma: Employee David Griffith, n/a, Qpex Biopharma: Employee.